A Hole Delocalization Strategy: Photoinduced Mixed-Valence MLCT States Featuring Extended Lifetimes - Aramburu-Troselj, Bruno M.; Oviedo, Paola S.; Pieslinger, German E.; Hodak, Jose H.; Baraldo, Luis M.; Guldi, Dirk Michael; Cadranel, Alejandro (Inorganic Chemistry, 2019)
Bimetallic trans-[RuII(tpm)(bpy)(μNC)RuII(L)4(CN)]2+, where bpy is 2,2′-bipyridine, tpm is tris(1-pyrazolyl)methane and L = 4-methoxypyridine (MeOpy) or pyridine (py), was examined using ultrafast vis-NIR transient absorption spectroscopy. Of great relevance are the longest-lived excited states in the form of strongly coupled photoinduced mixed-valence systems, which exhibit intense photoinduced absorptions in the NIR and are freely tunable by the judicious choice of the coordination spheres of the metallic ions. Using the latter strategy, we succeeded in tailoring the excited state lifetimes of bimetallic complexes and, in turn, achieving significantly longer values relative to related monometallic complexes. Notable is the success in extending the lifetimes, when considering the higher density of vibrational states, as they are expected to facilitate nonradiative ground-state recovery.
CRIS-Team Scopus Importer:2019-09-17